The use of the mobile phone in english classes in upper basic students at unidad educativa fiscal La Pila: a challenge or an opportunity - Cedeño Burgos, Erika Stefania (2023)
ICTs can carry out support missions for the reform of foreign language teaching-learning in Ecuador if their perception is reconsidered within a global framework that recognizes this capacity and conditions are created for their real use. Thus, the deficiencies linked to the flagrant lack of manuals for English lessons in basic education could be mitigated by making responsible use of the opportunities offered by the WhatsApp mobile application. These ICT resources would serve as educational materials to complement the official program. The article analyzes its potential and feasibility and also proposes guidelines for the teacher.